Recurrent Loss of Heterozygosity in Pancreatic Neuroendocrine Tumors. (4th June 2022) - Parilla, Megan; Chapel, David; Hechtman, Jaclyn F.; Wanjari, Pankhuri; El Jabbour, Tony; Sharma, Aarti; Ritterhouse, Lauren; Segal, Jeremy; Vanderbilt, Chad; Klimstra, David S.; Setia, Namrata; Tang, Laura
Abstract : Chromosomal aneuploidies are prognostic markers across a wide variety of tumor types, and recent literature suggests that pancreatic neuroendocrine tumors are no different. In this study 214 patients with grade 1, 2, or 3 pancreatic neuroendocrine tumors had their tissue examined for chromosomal copy number alterations using next-generation sequencing. Univariate and multivariate statistical analyses were performed with all-cause mortality and disease-specific mortality as the end comparators. As such, the cohort stratified into 3 different clinically relevant chromosomal subgroups: an indolent subgroup characterized by loss of chromosome 11 in relative isolation, an aggressive subgroup characterized by losses of chromosomes 1, 2, 3, 6, 10, 11, 16, and 22 and with no loss of chromosomes 4, 5, 7, 12, 14, 17, 19, and 20, and finally a heterogeneous third group with a subset of cases that behave even more aggressively than the aforementioned.